Phonetic training and non-native speech perception - New memory traces evolve in just three days as indexed by the mismatch negativity (MMN) and behavioural measures - Henna Tamminen; Maija S. Peltola; Teija Kujala; Risto Näätänen (ELSEVIER SCIENCE BV, 2022)
Language-specific, automatically responding memory traces form the basis for speech sound perception and new neural representations can also evolve for non-native speech categories. The aim of this study was to find out how a three-day phonetic listen-and-repeat training affects speech perception, and whether it generates new memory traces. We used behavioural identification, goodness rating, discrimination, and reaction time tasks together with mismatch negativity (MMN) brain response registrations to determine the training effects on native Finnish speakers. We trained the subjects the voicing contrast in fricative sounds. Fricatives are not differentiated by voicing in Finnish, i.e., voiced fricatives do not belong to the Finnish phonological system. Therefore, they are extremely hard for Finns to learn. However, only after three days of training, the native Finnish subjects had learned to perceive the distinction. The results show striking changes in the MMN response; it was significantly larger on the second day after two training sessions. Also, the majority of the behavioural indicators showed improvement during training. Identification altered after four sessions of training and discrimination and reaction times improved throughout training. These results suggest remarkable language-learning effects both at the perceptual and pre-attentive neural level as a result of brief listen-and-repeat training in adult participants.